Signs and symptoms of oral candidiasis associated with health factors and resistant Candida infections in a Northern Ontario patient cohort - Czajka, Karolina M.; Verschoor, Chris P.; Santi, Stacey A.; Brabant-Kirwan, Danielle; Kusnierczyk, Meredith H.; Venkataraman, Krishnan; Appanna, Vasu D.; Singh, Ravi; Tharmalingam, Sujeenthar; Saunders, Deborah P. (Frontiers in Oral Health, 2025)
BackgroundOral candidiasis is a common fungal infection that disproportionately affects older adults, immunosuppressed individuals, and patients undergoing cancer treatment. Despite its prevalence, diagnosis and treatment remain challenging due to the diverse symptom presentation and potential for antifungal resistance.ObjectiveThis study aimed to systematically evaluate which clinical signs and symptoms are most predictive of oral Candida infections, with a specific focus on identifying features associated with antifungal treatment failure. A secondary objective was to assess whether underlying medical conditions, including frailty and comorbidities, influence infection susceptibility or resolution following therapy.MethodsA cohort of 57 patients aged 65 years and older (mean age 74) was enrolled through oncology and hospitalist clinics in Northern Ontario. The majority (65%) were actively receiving cancer treatment. Participants underwent clinical assessment for oral candidiasis signs and symptoms, and fungal swabs were taken at baseline and two-week follow-up. Fungal species identification and treatment outcomes were recorded.ResultsThe majority of infections involved Candida albicans and responded to standard antifungal treatment. In contrast, infections involving Nakaseomyces glabratus and Pichia kudriavzevii tended to persist, consistent with known antifungal resistance. Symptomatically, pseudomembranous candidiasis—characterized by white plaques, coated tongue, and taste disturbance—was more likely to resolve, while erythematous features such as angular cheilitis and oral redness were associated with persistent infection. Although 45% of patients were classified as moderately to severely frail, frailty status was not significantly associated with infection persistence or resistance.ConclusionThese findings underscore the clinical variability of oral candidiasis and highlight the need for rapid molecular diagnostic tools at the point of care to distinguish infection types and guide appropriate therapy, particularly in older and medically complex populations.